Coating type monolithic catalyst as well as preparation method and application thereof
The coating-type monolithic catalyst is prepared by combining thickener and dispersant, which solves the problems of high coating shedding rate and poor dispersion of precious metals, and achieves efficient VOCs catalytic oxidation performance and cost reduction.
Patent Information
- Application Number
- CN202510502850.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-22
- Publication Date
- 2025-08-08
AI Technical Summary
The existing coated monolithic precious metal catalysts have insufficient loading strength on the surface of cordierite support, high coating shedding rate, poor dispersion of precious metals, resulting in poor catalytic performance and high cost.
The catalyst coating slurry with a slurry particle size of 0.5-3 μm was prepared by combining thickener, binder and dispersant. The slurry was coated on the cordierite carrier by vacuum extraction and then dried and calcined to form a solid coating.
Significantly reduce the coating shedding rate, improve the mechanical strength of the catalyst and the dispersion of precious metals, enhance catalytic activity, and reduce the cost of using precious metals.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of VOCs catalytic oxidation catalysts, and in particular to a coated integral catalyst for VOCs catalytic oxidation, a preparation method thereof, and an application thereof. Background Art
[0002] With the rapid development of industrialization, the emission of volatile organic compounds (VOCs) has continued to increase, causing serious impacts on the environment and human health.
[0003] VOCs are a diverse group of pollutants, with emissions spanning a wide range. Industrial production processes are the primary source of VOC emissions. Recent research indicates that typical VOCs, including aldehydes and ketones, are key pollutants in the formation of O₃ and secondary organic aerosols. Furthermore, VOCs have high atmospheric reactivity and a high ozone formation potential. Therefore, reducing and controlling VOC emissions from industrial sources is of great importance. Catalytic oxidation technology, as a low-energy, economical, and environmentally friendly approach, is one of the most effective methods for reducing and controlling VOC emissions. Currently, VOC remediation catalysts are primarily coated monolithic precious metal catalysts. These catalysts, which combine a ceramic support with a metal oxide, offer advantages such as high mechanical strength, excellent thermal conductivity, and low pressure drop, making them an optimal choice for treating industrial VOC exhaust. However, coating performance is often affected by slurry additives, resulting in high coating shedding rates, poor precious metal distribution, and low pore density. Therefore, the surface coating technology for coated monolithic precious metal catalysts requires further research and urgent improvement. One of the technical challenges in preparing loaded precious metal catalysts for VOCs treatment is stability. In the existing technology for preparing integral coated precious metal catalysts, the slurry performance is poor, the loading firmness of the coating after coating is not high, and the coating is prone to falling off during use. In addition, it is easy to aggregate to form larger precious metal particles with poor dispersion, thereby reducing the utilization rate of precious metal atoms, resulting in poor catalytic performance and the need to load more precious metals, resulting in high costs for the use of precious metals.
[0004] From an application perspective, coated monolithic precious metal catalysts used for VOCs treatment exhibit high activity at low temperatures and have good prospects for industrial application. Coated monolithic precious metal catalysts are usually prepared by coating with precious metal slurries, but traditional coating methods make it difficult to achieve uniform dispersion and strong adhesion of active components on the carrier. The biggest problem currently existing in the surface coating loading technology of coated monolithic catalysts is that the bonding strength between the carrier and the coating is weak, and it is easy to fall off under high-speed air blowing, especially TiO2, which is difficult to load on the surface of cordierite. At present, there are still many technical blind spots in the preparation process and mature products of coated monolithic catalysts in China. Summary of the Invention
[0005] In response to at least one shortcoming of the prior art, the present invention provides a coated monolithic catalyst, a preparation method and an application thereof. The coated monolithic catalyst is prepared by the preparation method of the present invention, which can significantly improve the loading firmness of the catalyst coating on the surface of the cordierite carrier, significantly reduce the coating shedding rate, have high mechanical strength, and at the same time take into account a good slurry loading rate.
[0006] To achieve its purpose, the present invention provides the following technical solutions:
[0007] In one aspect, the present invention provides a method for preparing a coated monolithic catalyst, comprising the following steps:
[0008] S1, stirring a thickener in water to prepare a thickener solution with a viscosity of 80-120cp, wherein the thickener is selected from one or more of hydroxyethyl methylcellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, and polyvinyl alcohol;
[0009] S2. Adding a binder, a dispersant, and a powdered catalyst to the thickener solution and stirring and dispersing the mixture, grinding the resulting mixed liquid to obtain a catalyst coating slurry with a slurry particle size D50 between 0.5 and 3 μm;
[0010] Based on the total mass of the catalyst coating slurry, the content of the binder is 5-20%, the content of the thickener is 0.1-3%, preferably 0.1-2.5%, the content of the dispersant is 0.1-3%, and the content of the powder catalyst is 15-20%;
[0011] S3, coating the catalyst coating slurry on a cordierite carrier, and then drying and calcining.
[0012] Preferably, the thickener is prepared by compounding hydroxyethyl methyl cellulose and polyvinyl alcohol in a mass ratio of (1-15):1, preferably the mass ratio is (1-10):1, and more preferably the mass ratio is (2-8):1.
[0013] Preferably, in step S1, the stirring is performed at 20-30°C, and the stirring time is preferably 2-3 hours.
[0014] Preferably, the binder is selected from one or more of aluminum sol, silica sol, and phosphate aluminum sol;
[0015] And / or, the cordierite carrier is a honeycomb cordierite carrier;
[0016] And / or, the dispersant is selected from one or more of oxalic acid, Tween 20, sodium tripolyphosphate, and polyethylene glycol.
[0017] In a preferred embodiment, based on the total mass of the catalyst coating slurry, the content of the thickener is 0.1-2.5%, and the content of the dispersant is 0.1-0.4%; the thickener is hydroxyethyl methyl cellulose and polyvinyl alcohol in a mass ratio of (2-8):1; and the binder is silica sol.
[0018] In some embodiments, the powder catalyst contains titanium dioxide.
[0019] Preferably, the powder catalyst comprises an active component, a catalytic promoter and a carrier, and the carrier comprises titanium dioxide;
[0020] The active component is selected from noble metal elements, preferably platinum; the catalyst promoter is selected from one or more of cerium oxide, lanthanum oxide, and niobium oxide;
[0021] Preferably, in the powder catalyst, the mass percentage of the active component is 0.1-1.5%, the mass percentage of the catalytic promoter is 5%-25%, and the mass percentage of the carrier is 73.5-94.9%.
[0022] Preferably, in step S3, the coating is performed by vacuum extraction coating.
[0023] Preferably, the calcination is carried out at 500-600° C., and the calcination time is preferably 2-6 hours.
[0024] Another aspect of the present invention provides a coated monolithic catalyst prepared by the preparation method described above. Preferably, the coated monolithic catalyst is a VOCs oxidation catalyst.
[0025] In another aspect, the present invention provides use of the above-mentioned coated monolithic catalyst in the catalytic oxidation of VOCs.
[0026] The technical solution provided by the present invention has the following beneficial effects:
[0027] 1. The slurry of the present invention has strong adhesion to the cordierite carrier, the coating shedding rate is low, and the catalyst has high mechanical strength. The preparation method of the present invention can obtain a good slurry loading rate without multiple coatings, which can solve the problem that traditional coating technology requires multiple coatings.
[0028] 2. The preparation method of the present invention can effectively solve the technical problem that TiO2 is difficult to load on the surface of the cordierite carrier, and can obtain a coated monolithic catalyst with both a low shedding rate and a good loading amount.
[0029] 3. The active component particles on the surface and in the pores of the coated monolithic catalyst of the present invention are highly dispersed. After high-temperature calcination, no particle agglomeration occurs, which can enhance the dispersion of precious metals, thereby increasing the surface active sites, which is beneficial to improving the catalytic oxidation activity, while effectively reducing the cost of precious metal catalysts. DETAILED DESCRIPTION
[0030] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention pertains. The term "and / or" as may be used herein includes any and all combinations of one or more of the associated listed items.
[0032] For numerical ranges, the endpoints of each range, the endpoints of each range and the individual points, and the individual points can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.
[0033] In one aspect, the present invention provides a method for preparing a coated monolithic catalyst, comprising the following steps:
[0034] S1. Stirring a thickener in water to prepare a thickener solution having a viscosity of 80-120 cp (e.g., 80 cp, 90 cp, 100 cp, 110 cp, 120 cp), wherein the thickener is selected from one or more of hydroxyethyl methyl cellulose (HEMC), sodium carboxymethyl cellulose, hydroxyethyl cellulose (HEC), and polyvinyl alcohol (PVA);
[0035] S2. Add a binder, a dispersant, and a powdered catalyst to the thickener solution, stir and disperse, and grind the resulting mixture to obtain a catalyst coating slurry having a slurry particle size D50 between 0.5 and 3 μm (e.g., 0.5, 1, 2, or 3 μm);
[0036] Based on the total mass of the catalyst coating slurry, the content of the binder is 5-20% (for example, 5%, 7%, 10%, 15%, 20%), the content of the thickener is 0.1-3% (for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%), the content of the dispersant is 0.1-3% (for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%), and the content of the powder catalyst is 15-20% (for example, 15%, 17%, 19%, 20%); in some examples, the remainder of the catalyst coating slurry is water.
[0037] S3, coating the catalyst coating slurry on a cordierite carrier, and then drying and calcining.
[0038] The preparation method of the present invention is to first prepare a thickener into a thickener solution with a viscosity of 80-120cp, then add other components to disperse, and control the mass ratio of each component in the coating slurry to be within the above range, and then grind it into a coating slurry with a slurry particle size D50 between 0.5-3μm; the coating slurry obtained by combining the above-mentioned unique batching method, the order of addition and the proportion of each component is coated on the cordierite carrier, and a good loading rate can be obtained without too many coating times, and there is strong adhesion between the coating and the carrier, the coating firmness is good, the coating shedding rate can be significantly reduced, and the catalyst mechanical strength is high; and the active component particles on the surface and pores of the obtained coated monolithic catalyst are highly dispersed, and after high-temperature calcination, no particle agglomeration occurs, which is beneficial to increase the surface active sites, and helps to effectively reduce the cost of the precious metal catalyst while improving the catalytic oxidation activity. The preparation method of the present invention can effectively overcome the problems of low catalyst coating loading firmness, low slurry loading rate and / or the need for more coating times on the surface of the honeycomb cordierite carrier in the prior art.
[0039] Preferably, based on the total mass of the catalyst coating slurry, the content of the thickener is 0.1-2.5%. Using the preferred amount of thickener is conducive to obtaining a lower shedding rate.
[0040] Preferably, in step S1, the thickener is hydroxyethyl methyl cellulose and polyvinyl alcohol in a mass ratio of (1-15): 1, preferably (1-10): 1; more preferably, the mass ratio of hydroxyethyl methyl cellulose and polyvinyl alcohol is (2-8): 1. Under other conditions being equivalent, the use of this preferred compound thickener is beneficial to further significantly reduce the coating shedding rate compared to a single thickener or compared to other compound systems, while taking into account a good slurry loading rate.
[0041] Preferably, in step S1, the stirring is carried out at 20-30°C (e.g., 20, 25, 30°C), and the preferred stirring time is 2-3h (e.g., 2h, 2.5h, 3h). The inventors have found that by preparing the thickener solution at the above-mentioned preferred temperature and stirring time, not only the thickener has good solubility, but also a thickener solution with the required viscosity of 80-120cp can be obtained. If the temperature is too low or too high, the dissolution effect and / or viscosity will be affected. The present invention pre-prepares a thickener solution with a viscosity of 80-120cp, and then adds other components to obtain a slurry in which the components are well dispersed; if the viscosity is too low or too high, it will be difficult to obtain a good coating effect, affecting the coating firmness.
[0042] Preferably, the binder is selected from one or more of aluminum sol, silica sol, and phosphorus aluminum sol, preferably aluminum sol;
[0043] Preferably, the cordierite carrier is a honeycomb cordierite carrier.
[0044] The method of the present invention can effectively overcome the technical problem that powder catalysts containing titanium dioxide are difficult to load on the surface of a honeycomb cordierite carrier. By preparing a coating slurry using the method of the present invention, the slurry prepared with a powder catalyst containing titanium dioxide can form a strong adhesion on the surface of a monolithic honeycomb cordierite carrier, forming a coating with good firmness, significantly reducing the coating shedding rate, and at the same time achieving a good slurry loading rate.
[0045] Preferably, the dispersant is selected from one or more of oxalic acid, Tween 20, sodium tripolyphosphate, and polyethylene glycol.
[0046] In a more preferred embodiment, the thickener content is 0.1-2.5% and the dispersant content is 0.1-0.4% based on the total mass of the catalyst coating slurry. The thickener is a mixture of hydroxyethyl methylcellulose and polyvinyl alcohol in a mass ratio of (2-8):1. The binder is silica sol. This preferred method for preparing the catalyst coating slurry can significantly reduce the coating shedding rate while also achieving an optimal loading rate.
[0047] In the present invention, there is no special restriction on the specific selection of the powder catalyst, and it can be selected according to the specific application requirements. The powder catalyst can be prepared by methods well known in the art, and is preferably a catalyst suitable for the catalytic oxidation of VOCs, especially a powder catalyst containing titanium dioxide. In traditional coating technology, titanium dioxide is difficult to load on the surface of the cordierite carrier, but the preparation method of the present invention can well overcome this technical difficulty. For the powder catalyst containing titanium dioxide, the preparation method of the present invention can form a better bonding strength between the cordierite carrier and the coating, thereby obtaining a coating with good firmness, a lower shedding rate and a higher loading rate.
[0048] In some specific embodiments, the catalyst powder includes an active component, a catalytic promoter, and a carrier, wherein the carrier includes titanium dioxide; the active component is selected from a precious metal element, preferably platinum; the catalytic promoter is selected from one or more of cerium oxide, lanthanum oxide, and niobium oxide, for example, one or more of CeO2, La2O3, and Nb2O5. In some preferred examples, in the powdered catalyst, the mass percentage of the active component is 0.1-1.5% (e.g., 0.1%, 0.5%, 1%, 1.5%), the mass percentage of the catalytic promoter is 5-25% (e.g., 5%, 10%, 15%, 20%, 25%), and the mass percentage of the carrier is 73.5-94.9% (e.g., 73.5%, 80%, 85%, 90%, 94.9%).
[0049] Preferably, in step S3, the coating is performed using a vacuum extraction coating method. Specifically, for example, the catalyst coating slurry is evenly spread on the upper surface of the honeycomb cordierite support, and then a vacuum device is used to extract the catalyst slurry from the lower end of the honeycomb cordierite support. The honeycomb cordierite support is then inverted and the extraction process is repeated to complete the coating process. The present invention can achieve a good slurry loading rate without requiring multiple coatings.
[0050] Preferably, in step S3, the calcination is carried out at 500-600°C (eg, 500°C, 550°C, 600°C), and the calcination time is preferably 2-6h (eg, 2h, 4h, 6h).
[0051] Another aspect of the present invention provides a coated monolithic catalyst prepared by the preparation method described above. Preferably, the coated monolithic catalyst is a VOCs oxidation catalyst.
[0052] In another aspect, the present invention provides use of the coated monolithic catalyst described above in the catalytic oxidation of VOCs.
[0053] The present invention is further described below by way of examples, but it should not be understood that the present invention is limited thereto.
[0054] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. Reagents or instruments used without specifying the manufacturer are all commercially available conventional products.
[0055] The test methods involved in the following examples and comparative examples are described as follows:
[0056] Shedding rate test: Take the coated integral catalyst samples prepared in the examples and comparative examples, cut them into sizes of 25mm*25mm*50mm, place them in an oven at 110°C and dry them for 30 minutes, then take them out of the oven and naturally cool them to room temperature in a desiccator, then weigh them, recorded as M1; at a distance of 1.5 cm from the end face of the catalyst sample, use 0.55MPa oil-free compressed air to evenly and slowly blow the catalyst end face until no obvious dust falls off, and test the mass of the sample after blowing, M2, where the shedding rate is equal to the ratio of the coating loss to the coating mass of the catalyst, and the calculation formula for the shedding rate is: μ=(M1-M2) / M3×100%, where μ is the shedding rate, M1 is the mass of the catalyst sample before the test; M2 is the mass of the catalyst sample after the test; M3 is the coating mass in the catalyst, and the test results are shown in Table 2.
[0057] The calculation formula of the coating mass is: M3=M1-M0, where M1 is the mass of the catalyst sample; M0 is the mass of the honeycomb cordierite carrier.
[0058] The calculation formula of the loading rate is: (M1-M0) / M0×100%, where M1 is the mass of the catalyst sample; M0 is the mass of the honeycomb cordierite support.
[0059] Test of viscosity of thickener solution: The slurry to be measured was placed in a beaker and tested at 25° C. The viscometer used was LVDV-1T manufactured by Shanghai Fangrui Instrument Co., Ltd.
[0060] The slurry particle size D50 test of the catalyst coating slurry was as follows: 2 ml of the slurry was placed in a beaker, and 50 ml of a 0.5 wt% sodium hexametaphosphate aqueous solution was added for dilution, and ultrasonicated for 3 minutes; an appropriate amount of sample was taken and added to a laser particle size analyzer for analysis and testing.
[0061] The powder catalysts used in the following examples and comparative examples were prepared according to the following steps:
[0062] First, the precious metal and the additive are prepared into a precursor solution, and then the precursor solution is added into titanium dioxide and mixed, and then the precious metal powder catalyst is obtained after heat concentration, drying and roasting in sequence;
[0063] (1) 0.55 g of platinum tetrachloride was dissolved in a 20 wt% aqueous hydrochloric acid solution on a 60° C. electric heating plate to obtain a precursor solution I; 40.37 g of cerium nitrate, 10.66 g of lanthanum nitrate, and 3.24 g of niobium oxalate were dissolved in a 20 wt% aqueous nitric acid solution in a 90° C. water bath to obtain a precursor solution II;
[0064] (2) Precursor solution I and precursor solution II were mixed, and 135 g of titanium dioxide (anatase type) was added. After heating and concentrating at 150° C. using an electric heating plate, the mixture was dried in an oven at 105° C. for 4 h, and then calcined in a muffle furnace at 600° C. for 6 h to prepare a powder catalyst. The composition of the powder catalyst is shown in Table 1 below:
[0065] Table 1
[0066] Components Pt <![CDATA[CeO2]]> <![CDATA[La2O3]]> <![CDATA[Nb2O5]]> <![CDATA[TiO2]]> Proportion, mass percentage 0.2% 10% 5% 1% 83.8%
[0067] Example 1
[0068] The coated monolithic catalyst was prepared as follows:
[0069] S1. Slowly add 5 g of hydroxyethyl methyl cellulose (HEMC) and 1 g of polyvinyl alcohol (PVA) in batches to 730 g of deionized water, stir with a stirring paddle at 25° C. for 2-3 h, and measure the solution viscosity to 100 cp to obtain a thickener solution;
[0070] S2. Add 100 g of silica sol (solid content 30 wt%) and 3 g of Tween 20 to the thickener solution and stir for 1 hour. Then add 161 g of the powdered catalyst and continue stirring for 2 hours. Then, grind the mixture using a horizontal sand mill for 1 hour until the slurry particle size D50 is between 0.5 and 1 μm, thereby obtaining a catalyst-coated slurry. The mass ratio of silica sol: hydroxyethyl methylcellulose: polyvinyl alcohol: Tween 20 in the slurry is 100:5:1:3.
[0071] S3. Coating is performed by vacuum extraction coating. About 100 g of slurry is evenly spread on the upper surface of a 150 mm * 150 mm * 50 mm honeycomb cordierite carrier. A vacuum extraction device is used at the lower end of the honeycomb cordierite carrier to extract until the slurry is completely coated in the pores. The catalyst is then turned upside down and the previous extraction operation is repeated. After that, the catalyst is placed in an oven at 110 ° C. to dry for 2 h, and then calcined in a muffle furnace at 550 ° C. for 6 h to obtain a coated monolithic catalyst.
[0072] Example 2
[0073] The process was carried out in accordance with Example 1, except that the amount of Tween 20 added was adjusted, and the mass proportion of Tween 20 in the catalyst coating slurry was 0.5%.
[0074] Example 3
[0075] The process was carried out in accordance with Example 1, except that the addition amounts of hydroxyethyl methyl cellulose (HEMC) and polyvinyl alcohol (PVA) were adjusted, and the mass proportions of hydroxyethyl methyl cellulose (HEMC) and polyvinyl alcohol (PVA) in the catalyst coating slurry were 1.5% and 0.1%, respectively.
[0076] Example 4
[0077] The process was carried out in accordance with Example 1, except that the addition amounts of hydroxyethyl methyl cellulose (HEMC) and polyvinyl alcohol (PVA) were adjusted, and the mass proportions of hydroxyethyl methyl cellulose (HEMC) and polyvinyl alcohol (PVA) in the catalyst coating slurry were 0.5% and 0.5%, respectively.
[0078] Example 5
[0079] The process was carried out in accordance with Example 1, except that the addition amounts of hydroxyethyl methyl cellulose (HEMC) and polyvinyl alcohol (PVA) were adjusted, and the mass proportions of hydroxyethyl methyl cellulose (HEMC) and polyvinyl alcohol (PVA) in the catalyst coating slurry were 0.1% and 0.1%, respectively.
[0080] Example 6
[0081] The process was carried out in accordance with Example 1, except that the addition amounts of hydroxyethyl methyl cellulose (HEMC) and polyvinyl alcohol (PVA) were adjusted, and the mass proportions of hydroxyethyl methyl cellulose (HEMC) and polyvinyl alcohol (PVA) in the catalyst coating slurry were 2.5% and 0.5%, respectively.
[0082] Example 7
[0083] The process was carried out in accordance with Example 1, except that the amount of Tween 20 added was adjusted, and the mass proportion of Tween 20 in the catalyst coating slurry was 2%.
[0084] Example 8
[0085] The process was carried out in accordance with Example 1, except that the type of binder was adjusted, the silica sol was changed to alumina sol, and the mass proportion of alumina sol in the catalyst coating slurry was 10%.
[0086] Example 9
[0087] The method was carried out in accordance with Example 1, except that the type of thickener was adjusted by replacing hydroxyethyl methyl cellulose (HEMC) with sodium carboxymethyl cellulose (CMC), and the mass proportion of sodium carboxymethyl cellulose (CMC) in the catalyst coating slurry was 0.5%.
[0088] Example 10
[0089] The method was carried out in accordance with Example 1, except that a single thickener was used, namely, only hydroxyethyl methyl cellulose (HEMC) was added, and the mass proportion of hydroxyethyl methyl cellulose (HEMC) in the catalyst coating slurry was 0.5%.
[0090] Comparative Example 1
[0091] The process was carried out in accordance with Example 1, except that the amount of silica sol added was adjusted so that the mass proportion of silica sol in the catalyst coating slurry was 25%.
[0092] Comparative Example 2
[0093] The same procedures were followed as in Example 1, except that in step S1, stirring was performed at 25°C for 1 hour, resulting in a thickener solution with a viscosity of 60 cps. All other steps were followed as in Example 1 and are not further described. The resulting coated monolithic catalyst was tested, and the shedding rate was 17.20% and the loading rate was 14.37%.
[0094] Comparative Example 3
[0095] The same process as in Example 1 was followed, except that in step S2, the particle size D50 of the catalyst coating slurry obtained after grinding was 3.1-4.5 μm. All other steps were similar to those in Example 1 and are not further described. The resulting coated monolithic catalyst was tested, and the shedding rate was 15.41% and the loading rate was 14.62%.
[0096] The mass percentages of some components in the catalyst coating slurry and the test results of the coated monolithic catalyst in the above examples and comparative examples are summarized in Table 2:
[0097] Table 2
[0098]
[0099] No particle agglomeration was observed in the coated monolithic catalysts prepared in the aforementioned Examples, while significant particle agglomeration was observed in the monolithic catalysts prepared in Comparative Examples 1 and 3. A comparison of the results of the aforementioned Examples and Comparative Examples reveals that the coated monolithic catalysts prepared in the Examples of the present invention exhibit significantly lower shedding rates (<10.5%), excellent mechanical strength, and a good loading rate (>11.5%).
[0100] It will be readily understood that the above embodiments are merely examples for clarity of description and are not intended to limit the present invention to these examples. Those skilled in the art will readily appreciate that other variations or modifications based on the above description are possible. It is not necessary and impossible to provide an exhaustive list of all possible implementations. Obvious variations or modifications arising therefrom remain within the scope of protection of the present invention.
Claims
1. A method for preparing a coated monolithic catalyst, characterized in that: The steps include: S1, stirring a thickener in water to prepare a thickener solution with a viscosity of 80-120cp, wherein the thickener is selected from one or more of hydroxyethyl methylcellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, and polyvinyl alcohol; S2. Adding a binder, a dispersant, and a powdered catalyst to the thickener solution and stirring and dispersing the mixture, grinding the resulting mixed liquid to obtain a catalyst coating slurry with a slurry particle size D50 between 0.5 and 3 μm; Based on the total mass of the catalyst coating slurry, the content of the binder is 5-20%, the content of the thickener is 0.1-3%, the content of the dispersant is 0.1-3%, and the content of the powder catalyst is 15-20%; S3, coating the catalyst coating slurry on a cordierite carrier, and then drying and calcining.
2. The preparation method according to claim 1, characterized in that The thickener is prepared by compounding hydroxyethyl methyl cellulose and polyvinyl alcohol in a mass ratio of (1-15):1, preferably the mass ratio is (1-10):1, and more preferably the mass ratio is (2-8):
1.
3. The preparation method according to claim 1 or 2, characterized in that In step S1, the stirring is performed at 20-30°C, and the preferred stirring time is 2-3 hours.
4. The preparation method according to any one of claims 1 to 3, characterized in that The binder is selected from one or more of aluminum sol, silica sol, and phosphorus aluminum sol; And / or, the cordierite carrier is a honeycomb cordierite carrier; And / or, the dispersant is selected from one or more of oxalic acid, Tween 20, sodium tripolyphosphate, and polyethylene glycol; And / or, based on the total mass of the catalyst coating slurry, the content of the thickener is 0.1-2.5%.
5. The preparation method according to any one of claims 1 to 4, characterized in that Based on the total mass of the catalyst coating slurry, the content of the thickener is 0.1-2.5%, and the content of the dispersant is 0.1-0.4%; The thickener is prepared by mixing hydroxyethyl methyl cellulose and polyvinyl alcohol in a mass ratio of (2-8):1; The binder is silica sol.
6. The preparation method according to any one of claims 1 to 5, characterized in that The powder catalyst contains titanium dioxide; Preferably, the powder catalyst comprises an active component, a catalytic promoter and a carrier, and the carrier comprises titanium dioxide; The active component is selected from noble metal elements, preferably platinum; the catalyst promoter is selected from one or more of cerium oxide, lanthanum oxide, and niobium oxide; Preferably, in the powder catalyst, the mass percentage of the active component is 0.1-1.5%, the mass percentage of the catalytic promoter is 5%-25%, and the mass percentage of the carrier is 73.5-94.9%.
7. The preparation method according to any one of claims 1 to 6, characterized in that In step S3, the coating is performed by vacuum extraction coating.
8. The preparation method according to any one of claims 1 to 7, characterized in that The calcination is carried out at 500-600° C., and the preferred calcination time is 2-6 hours. 9 . A coated monolithic catalyst prepared by the preparation method according to claim 1 , wherein the coated monolithic catalyst is a VOCs oxidation catalyst.
10. Use of the coated monolithic catalyst according to claim 9 in the catalytic oxidation of VOCs.